2005
DOI: 10.1152/ajplung.00032.2005
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of CCL26 synthesis and secretion in A549 cells: a possible mechanism by which alveolar epithelial cells modulate airway inflammation

Abstract: Eotaxins (CCL11, CCL24, CCL26) originating from airway epithelial cells and leukocytes have been detected in bronchoalveolar lavage of asthmatics. Although the alveolar epithelium is the destination of uncleared allergens and other inflammatory products, scanty information exists on their contribution to the generation and regulation of the eotaxins. We envisioned a state whereby alveolar type II cells, a known source of other inflammatory proteins, could be involved in both the production and regulation of CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
1
23
1
Order By: Relevance
“…Although chemokine up-regulation induced by CCL11 was not inhibited in this study by CCR3 antagonism, autoregulation of CCR3 by CCL11 and CCL26 has been previously reported in normal bronchial EC and in the alveolar EC line A549, respectively (50,51), suggesting the existence of a complex regulatory feedback system, similar to that documented for other receptors, such as the high-affinity IgE receptor (52,53). A complex role of CCR3 in regulating local chemokine levels is further suggested by the reported involvement of the CCR3 expressed on human dermal microvascular EC in mediating the suppression of TNF-␣-induced CXCL8 in cells treated with CCL11 (54).…”
Section: Discussioncontrasting
confidence: 58%
“…Although chemokine up-regulation induced by CCL11 was not inhibited in this study by CCR3 antagonism, autoregulation of CCR3 by CCL11 and CCL26 has been previously reported in normal bronchial EC and in the alveolar EC line A549, respectively (50,51), suggesting the existence of a complex regulatory feedback system, similar to that documented for other receptors, such as the high-affinity IgE receptor (52,53). A complex role of CCR3 in regulating local chemokine levels is further suggested by the reported involvement of the CCR3 expressed on human dermal microvascular EC in mediating the suppression of TNF-␣-induced CXCL8 in cells treated with CCL11 (54).…”
Section: Discussioncontrasting
confidence: 58%
“…32,[42][43][44][45] In this regard, we tested whether IL-13 would induce the expression of CCL26 and other CC chemokines by human primary BECs obtained from healthy control subjects and patients with mild or severe asthma. Clinical characteristics of these subjects are presented in Table I.…”
Section: Il-13 Selectively Increases Expression Of Ccl26 By Human Primentioning
confidence: 99%
“…IL-13 is not a known chemoattractant for neutrophils but for eosinophils; this is an effect that may be mediated through the release of the eosinophil chemokine, eotaxin/CCL13 [35,36]. It has been reported that patients with allergic rhinitis exposed to ozone experimentally produce an eosinophilic response [37,38].…”
Section: Il-13 and Ozone As Williams Et Almentioning
confidence: 99%